Quasi-Gaussian Multibeam Solar Laser Station for a Megawatt Solar Furnace (Journal of Solar Energy Research Updates, 2021)
An alternative multirod solar side-pumping concept for the production of multiple quasi-Gaussian beams is proposed. This scheme was based on the One-Megawatt solar furnace in Odeillo, France, which collected and concentrated the solar light into a multilayered pyramidal pumping cavity placed at the focal zone. Each layer was comprised of a square array of four laser heads, each composed of a biconic surface that reflected the solar rays towards a Nd:YAG rod fixed inside a fused silica flow tube. A pyramidal reflector was placed inside the pumping cavity to close it and maximize the harness of solar energy. Compared to the previous multibeam solar laser station design for the same solar furnace, considerable alleviation of thermal lensing effects was achieved with the present approach, allowing the improvement of the laser beam quality factors and, consequently, the possibility of a 32-laser-beam generation, each with a quasi-Gaussian profile. For this case, 9.44 kW total laser power was calculated. Additionally, 20.01 kW total multimode laser power was numerically determined, which corresponds to a 10.93 W/m2 collection efficiency and a 2.0% solar-to-laser power conversion efficiency.